2021
DOI: 10.1063/5.0050767
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearly enhanced photoacoustic microscopy by picosecond-laser-pumped excited state absorption of phthalocyanine nanoprobes

Abstract: Efficient nanoprobes with unique optical properties are highly desirable for good-performance photoacoustic (PA) molecular imaging. The conventionally used PA nanoprobes basically take their ground-state absorption with contrast to the indelible wideband background absorption as the imaging mechanism, thus severely limiting the imaging contrast and sensitivity in practical applications. Herein, a nonlinearly enhanced PA microscopy mechanism with suppressed background interference and improved brightness has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…They observed two-photon and three-photon absorption and reported coefficients of β eff 312 cmGW −1 and a γ eff 8.8 cm 3 GW −2 . Phthalocyanine nanoprobes were reported recently, and they have been demonstrated as highly desirable for photoacoustic molecular imaging (Li et al, 2021). Two-photon absorption coefficients of ∼10 −13 cm/W were reported for phthalocyanine porphyrin conjugates metalated with nickel by Xiao et al, 2016.…”
Section: Nonlinear Optical Measurementsmentioning
confidence: 99%
“…They observed two-photon and three-photon absorption and reported coefficients of β eff 312 cmGW −1 and a γ eff 8.8 cm 3 GW −2 . Phthalocyanine nanoprobes were reported recently, and they have been demonstrated as highly desirable for photoacoustic molecular imaging (Li et al, 2021). Two-photon absorption coefficients of ∼10 −13 cm/W were reported for phthalocyanine porphyrin conjugates metalated with nickel by Xiao et al, 2016.…”
Section: Nonlinear Optical Measurementsmentioning
confidence: 99%
“…As an emerging imaging technology, photoacoustic (PA) imaging combines the excellent contrast of optical imaging with the good tissue penetration of ultrasound through the conversion of photons to acoustic waves, and it has attracted tremendous attention in the biomedical field. Specifically, aided by a variety of nanomaterials with diversified morphologies and functions, PA imaging had been explored in depth with extended imaging function such as target molecule tracing, cellular environment monitoring, and specific contrast enhancement. In recent years, studies and experiments have shown that PA technology is capable of monitoring temperature in vivo based on the Grueneisen effect, where the PA signal amplitude grows linearly with temperature in a certain range. However, as the PA amplitude enhancement in tissue arising from the Grueneisen effect is quite small (∼4% enhancement for 1 °C temperature increase), the sensitivity and accuracy of the existing method still cannot satisfy the need for precise 3D temperature monitoring in deep-seated tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding interactions between light and medium is a longstanding issue in biomedical imaging [1,2], as it has fundamental importance to imaging techniques such as photoacoustic imaging [3][4][5][6]. Optical resolution photoacoustic microscopy (ORPAM) is a photoacoustic imaging modality, which has demonstrated diffraction-limited lateral resolution on the surface [7], subwavelength-resolution label-free imaging [8], and subdiffraction label-free imaging [9], despite typically limited penetration depth of 1-2 mm due to the tight optical focus of ballistic photons [10].…”
Section: Introductionmentioning
confidence: 99%